Indonesian EFL university students' metacognitive online reading strategies before and during the Covid-19 pandemic - Agus Rianto (Studies in English Language and Education, 2021)
This descriptive study focused on investigating the use of metacognitive online reading strategies that were associated with learning conditions before and during the Covid-19 Pandemic. The respondents were 244 Indonesian EFL students taking an English subject at the Borneo Tarakan University. Data were collected using the Online Survey of Reading Strategies (OSORS) through the application of Google Form. The collected data were analyzed descriptively and quantitatively. The results showed that before the pandemic, support strategies were used more frequently, while global strategies were used less frequently. During the pandemic, support strategies and problem-solving strategies were more dominantly used, while global strategies remained the least used. Although the students differed significantly in using the overall and categorical strategies, they did not have differences in using some of the individual strategies. The students were moderate users of the strategies before the pandemic and were high users during the pandemic. These results imply that EFL students need to have metacognitive awareness to help them better understand what they read online. This can be done by involving students more actively in the use of strategies, especially those that were not different when used before and during the Covid-19 pandemic.